2018
DOI: 10.9738/intsurg-d-16-00193.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of an Array of Routine Clinical Variables to the Occurrence and Severity of Postoperative Pneumonia in Non–Small Cell Lung Cancer Patients

Abstract: Background and purpose: Data of an array of preoperative/intraoperative clinical variables may carry significant information for predicting the probability of postoperative pneumonia or chest infection in non-small cell lung cancer (NSCLC) patients. We aimed to investigate the association between those variables and the occurrence of postoperative pneumonia (POP) as well as the severity of POP, based on routine laboratory tests, basic characteristics, and perioperative variables during the in-hospital period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…A high CCI is a risk factor for developing postoperative pneumonia (1,13). In their study, Shen et al reported that a high CCI score (>3) and a high American Society of Anesthesiologists (ASA) score (>3) were both risk factors for POP development and increased pop severity (16).…”
Section: Discussionmentioning
confidence: 99%
“…A high CCI is a risk factor for developing postoperative pneumonia (1,13). In their study, Shen et al reported that a high CCI score (>3) and a high American Society of Anesthesiologists (ASA) score (>3) were both risk factors for POP development and increased pop severity (16).…”
Section: Discussionmentioning
confidence: 99%